Treatment of Toenail Onychomycosis using Laser Pharmacology™ - Kerry Zang; Travis M Sammons; Steve Shanks (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2021)
Background: Onychomycosis is a common infection of the nail bed that can negatively affect patient quality of life. The complete cure rate for systemic drugs is 23-37 % while the complete cure rate for topical drug therapy with efinaconazole is 27.7%. Laser Pharmacology™ presents a promising alternative using a dual-diode laser employing wavelengths of 635 nm and 405 nm to create a drug-like response in living tissue (Erchonia® Lunula Laser®; Erchonia Corporation. Melbourne, FL). The purpose of this clinical study is to assess the safety and efficacy of mycological and complete cure rates of the dual diode nonthermal laser. Methods: Enrolled subjects (N=20) had onychomycosis affecting the great toenail, confirmed by a positive mycological culture. Subjects were predominantly female (70%) with a mean (SD) age of 59.9 (9.0) years. Affected toenails were treated with 12-minute laser light sessions, each week for 4 weeks, then one session at 3, 5, 7, 9 and 11 months. Study assessments were completed at 3, 5, 7, 9, 11, 12 and 14 months.  Results: Most subjects achieved a Clinical Cure (n=14, 70%) and Mycological Cure (n=19, 95%) of the affected great toenail. At 12 months, most subjects also achieved Clinical Efficacy (n=18, 90%), Mycological Cure (n=19, 95%) and unaffected New Nail Growth (n=20, 100%).  Conclusion: This study confirms the safety and effectiveness of a non-thermal 635 nm/405 nm dual-diode laser device for providing mycological and complete cure rate in onychomycosis-affected toenails following four weekly and five bi-monthly treatment sessions. Trial registration: ClinicalTrials.gov Identifier NCT03066336, registered 02/28/2017, https://clinicaltrials.gov/ct2/show/NCT03066336